Educational process factors for effective education in resource-constrained countries: a multilevel analysis. Issue 3 (2nd July 2020) - Mugendawala, Hamis; Muijs, Daniel
ABSTRACT: Earlier studies of educational effectiveness in resource-constrained countries tended to focus on fiscal and material resources. However, the impact thereof can be limited where effective processes at the school and classroom levels are not present. Using hierarchical linear modelling, this study draws on SACMEQ data to generate an effective education model for resource-constrained countries, using Uganda as a case study. Rasch modelling was used to construct the educational process indicators, and the dynamic model of educational effectiveness provided the basis for the conceptual framework used. On adjusting for confounding variables, the factors that significantly predicted both mathematics and reading outcomes included opportunity to learn (OTL), school management competences, school–community relationships, and school-based HIV/AIDS support. The effect of teacher academic and professional capital (TAPC) was mediated by OTL. The study argues for refocused attention on the school and teaching processes as key to enhancing educational effectiveness in resource-constrained countries.